Fibroblast heterogeneity and its role in generating protective immunity in the secondary lymphoid organs - Yasmin, Hadida; Ramesh, Remya P. G.; Joseph, Ann Mary; Kishore, Uday (Frontiers in Immunology, 2025)
Fibroblasts are cells of mesenchymal origin with a range of phenotypic diversity and heterogeneity. One of the major functions of fibroblasts is the formation and turnover of the extracellular matrix and establishing a tissue structure by forming a matrisome from embryonic development to the adult stage. It plays an indispensable role in extracellular matrix remodeling during injury, repair, and infection, providing a scaffold for cell-to-cell interaction. Despite their important pathophysiological roles, molecular markers for tissue-resident fibroblasts are only now being identified. Fibroblasts acquire molecular signatures based on anatomical locations, thus impacting their phenotypic heterogeneity despite their overlapping morphology. Fibroblasts are now recognized as key immune sentinel cells, capable of regulating the inflammatory milieu through their distinct functional subsets that are designed to respond differently with unique immune signatures. Fibroblasts can detect pathogenic and danger signals through their diverse pattern recognition receptors (PRRs) and release soluble mediators that can modulate the immune infiltrates at the site of tissue injury and repair. This review discusses the diversity and heterogeneity of fibroblasts in secondary lymphoid organs such as lymph nodes, spleen, and Peyer’s patches, and their contributions to a range of pathological and physiological processes. The role of trans-differentiated effector fibroblast phenotypes that modulate the expression and function of various innate immune components (PRRs, cytokines, chemokines, and complement) in maintaining homeostasis has also been discussed.